Flexible and / or foldable articles and methods for arranging flexible and / or foldable articles
Patent Information
- Application Number
- JP2020157794
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-05-02
- Filing Date
- 2020-09-18
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2038-09-03
Smart Images

Figure 0007648357000033 
Figure 0007648357000034 
Figure 0007648357000035
Abstract
Description
[Technical field]
[0001] The present invention relates to a flexible and / or foldable article, its use and to a method for arranging a flexible and / or foldable article. The article is made of a transparent brittle material, in particular glass, glass ceramic, ceramic or crystal. Such an article is used in particular as a display cover, in particular as a protective cover for a display, for example in smartphones or tablets or TV devices. Such an article can also be used as a substrate for electronic components, for example OLEDs or LEDs. [Background technology]
[0002] Brittle materials can only bend up to a certain load limit, which depends on many different material and strength parameters, and current articles still cannot achieve customer demands for desired bend radii.
[0003] The load cases encountered by flexible displays can be divided into three groups. 1) Tensile load due to bending 2) Impact loads, such as those caused by objects falling onto the display or products falling onto it 3) Load caused by scratching with hard objects, etc.
[0004] In the prior art, no article has been found with acceptable load-bearing properties. These load-bearing properties depend on a great number of different material and strength parameters, such as elastic modulus, Poisson's ratio, fracture toughness, compressive stress, characteristic indentation depth, article thickness, hardness, density, and properties at subcritical crack growth. The effects of these different parameters on the load-bearing properties are complex. Moreover, there are various interactions between these parameters. It has not been possible to optimize all of the parameters. It has also not been possible to identify, among these many parameters, the parameters that are particularly relevant for improving the load-bearing properties. Moreover, it is desirable to find not only the parameters that are particularly relevant, but also the relationships that exist between these parameters, which allow the parameters to be related and the load-bearing properties to be deduced from the relationships. Summary of the Invention [Problem to be solved by the invention]
[0005] The object of the present invention is to provide an article having an increased average life span when subjected to bending loads, and a method for providing such an article. By "increased average life span" it is meant that the article can withstand the loads mentioned in the present application for a longer period of time than the articles of the prior art. Such improved bendability allows smaller radii to be achieved without breaking. Thus, "increased average life span" also means that the article can be bent to smaller radii before breaking compared to the prior art. The object of the present invention is to provide an article which allows the article of the present invention to achieve a higher load (smaller bending radius) for the same failure probability, or conversely, an article in which the article of the present invention has a lower failure probability for a given load (bending radius), and a method for producing such an article. The object of the present invention is also to provide an article having an increased average life span when subjected to impact and / or scratch loads, and a method for providing such an article. Furthermore, the object of the present invention is in particular to provide an article having an increased average life span when subjected to bending and / or impact and / or scratch loads, and a method for providing such an article. [Means for solving the problem]
[0006] The above problems are solved by the present invention.
[0007] In one embodiment, the invention relates to a method for providing an article made of a transparent, brittle material with improved bending properties.
[0008] In one embodiment, the present invention provides a method for disposing an article made of a transparent brittle material, comprising the steps of: a) the following parameters of each item in the set of items: i. Fracture toughness K Ic ii. Compressive stress CS iii. Indentation depth characteristic value x c iv. Thickness of the article d and b) Among the set, the following formula:
number
number
number
number
number
[0009] When using this formula, length x c and d in meters, stresses CS and UeP in MPa, fracture toughness K Ic is used in units of MPa √m. The numbers 395, 0.843 and 2.37 are unitless. In the above formulas, tensile stresses should be used as positive numbers and compressive stresses as negative numbers. Therefore, the compressive stress CS is a negative number.
[0010] The above parameters of each item fracture toughness K Ic , compressive stress CS, indentation depth characteristic value x c The measurement of the thickness d of the article and the thickness d of the article do not necessarily have to be performed directly on every individual article. The measurement of the parameters of the individual articles can also be performed indirectly, for example, using one or more reference articles. In the present invention, the parameters of the present invention of the individual articles can be determined by measuring the parameters based on a reference article from which the parameters of the individual articles can be estimated. For example, the measurement of one or more parameters in a production lot can be performed not directly on the selected article itself, but on one or more reference articles of the same lot, as long as the difference in the parameters between the individual articles of the same lot is not significant or does not differ significantly. Here, "insignificant difference" preferably means that the difference between the maximum and minimum values in the same lot is at most 20%, more preferably at most 15%, more preferably at most 10%, more preferably at most 5%, more preferably at most 2%, and even more preferably at most 1%.
[0011] Particularly advantageously, the fracture toughness K of each article is determined using one or more reference articles. Ic Since the difference between the individual articles is particularly small with regard to this parameter, the fracture toughness K Ic is particularly suited for such indirect measurements.
[0012] In one embodiment, the invention relates to an article made of a transparent, brittle material having improved bending properties.
[0013] In one embodiment, the present invention provides an article made of a transparent brittle material, the article having a fracture toughness K Ic , the compressive stress CS, and the indentation depth characteristic value x c and the thickness of the article, d and for the article, the following formula:
number
number
number
number
number
[0014] The invention also includes a set of n articles having the above-mentioned properties. The number of articles n is advantageously at least 2, 3, 4, 5, 10, 20, 50 or even at least 100. Such a "set of articles" is characterized in that the articles are spatially grouped, routinely selected and arranged for another use. A "set of articles" advantageously does not include articles that do not have the above-mentioned properties, but only includes articles that have the above-mentioned properties. In particular, the term "set of articles" also advantageously means that the articles belonging to the set are spatially separated from other articles, if there are other articles that do not belong to the set of the invention because they do not have the above-mentioned properties. In particular, the articles belonging to the set of articles advantageously come from the same production lot.
[0015] A transparent material in the sense of the invention is preferably a material which, when it is 2 mm thick, has a net transmittance of electromagnetic waves in a 50 nm wide region of the 380-800 nm spectrum, particularly preferably a 250 nm wide region, of more than 25%, more preferably more than 60%, even more preferably more than 80%, even more preferably more than 90%, particularly preferably more than 95%.
[0016] Brittle materials according to the invention are advantageously those having a thickness of 0.1 μm -1 / 2 Super brittle S, more advantageously 0.2μm -1 / 2 More preferably, 0.5 μm -1 / 2 Ultra-fine, and even more advantageously 0.8 μm -1 / 2 Ultra-fine, and even more advantageously 1 μm -1 / 2 More preferably, 1.5 μm -1 / 2 Ultra-, and even more advantageously 2 μm -1 / 2 The material has a brittleness S of up to 20 μm. -1 / 2 , and more advantageously up to 18 μm -1 / 2 , and more preferably up to 15 μm -1 / 2 , and more preferably up to 12 μm -1 / 2 , and more preferably up to 10 μm -1 / 2 , and more advantageously up to 9 μm -1 / 2 , and more advantageously up to 8 μm -1 / 2 Advantageously, the brittleness S is less than 0.1 μm.-1 / 2 ~20μm -1 / 2 and more preferably in the range of 0.2 μm. -1 / 2 ~18μm -1 / 2 and more preferably in the range of 0.5 μm -1 / 2 ~15μm -1 / 2 and more preferably in the range of 0.8 μm -1 / 2 ~12μm -1 / 2 and more preferably in the range of 1 μm -1 / 2 ~10μm -1 / 2 and more preferably in the range of 1.5 μm -1 / 2 ~9μm -1 / 2 and more preferably in the range of 2 μm -1 / 2 ~8μm -1 / 2 Here, brittleness S is the sum of Vickers hardness H and fracture toughness K Ic Compared to S=H / K Ic This refers to.
[0017] This ratio is used as a measure of brittleness in the article by Lawn, BR; Marshall DB;; "Hardness, Toughness, and Brittleness: An Indentation Analysis"; Journal of the American Ceramic Society (1979). The person skilled in the art knows how to experimentally measure such brittleness. Advantageously, brittleness is measured according to the article by Sehgal, J.; Ito, S.; "Brittleness of glass"; Journal of Non-Crystalline Solids (1999)".
[0018] The transparent brittle material is advantageously selected from the group consisting of glasses, glass ceramics, ceramics and crystals. Advantageous crystals are those selected from the group consisting of sapphire, diamond, corundum, ruby, topaz, quartz and orthoclase. Sapphire is a particularly advantageous crystal. Particularly advantageously, the transparent brittle material is a glass or glass ceramic, and even more advantageously a glass. Particularly advantageously, the transparent brittle material is a borosilicate glass, an aluminosilicate glass or an aluminoborosilicate glass. Advantageously, the proportion of Li2O+Na2O in the material of the invention, in particular in the glass of the invention, is greater than 1% by weight, more advantageously greater than 3% by weight and even more advantageously greater than 5% by weight. In a particularly advantageous embodiment, the material of the invention, in particular the glass of the invention, contains Na2O but does not contain Li2O, Rb2O and Cs2O. In the present specification, when a material, particularly a glass, is said to be "free of a certain component" or "free of a particular component," this means that the component may be present in the material or glass as an impurity. That is, the component is not added or contained in a significant amount. Insignificant amounts are, in the present invention, amounts less than 1000 ppm, advantageously less than 500 ppm, and most advantageously less than 100 ppm.
[0019] When a brittle material is bent without any other protective mechanism, tensile stress is generated on the convex side, and when a threshold value is exceeded, this tensile stress causes fracture. In this application, the parameter fracture toughness K is set so that the durability parameter UeP in the above relational expression exceeds 250 MPa. Ic , compressive stress CS, indentation depth characteristic value x c It has been found that by selecting the thickness d of the article, a particularly flexible and / or foldable article is obtained. UeP has the dimension of tensile stress and is expressed in units of MPa. Surprisingly, then, the parameter fracture toughness K Ic , compressive stress CS, indentation depth characteristic value x cIt has been found that articles made of transparent brittle materials have a particularly long life under bending loads if the above-mentioned relationship holds between the article thickness d and the durability parameter UeP and if UeP is greater than 250 MPa. Advantageously, UeP is at least 300 MPa, more advantageously at least 350 MPa, more advantageously at least 400 MPa, more advantageously at least 450 MPa, very particularly advantageously at least 500 MPa, more advantageously at least 600 MPa, more advantageously at least 700 MPa, more advantageously at least 800 MPa. Advantageously, UeP is at most 1,000,000 MPa, more advantageously at most 100,000 MPa, more advantageously at most 20,000 MPa, more advantageously at most 10,000 MPa, more advantageously at most 7,500 MPa, more advantageously at most 5,000 MPa, more advantageously at most 4,000 MPa, more advantageously at most 3,000 MPa, more advantageously at most 2,000 MPa. Advantageously, UeP is in the range of greater than 250 MPa and up to 1,000,000 MPa, more advantageously 300 MPa to 100,000 MPa, even more advantageously 350 MPa to 20,000 MPa, even more advantageously 400 MPa to 10,000 MPa, even more advantageously 450 MPa to 7,500 MPa, even more advantageously 500 MPa to 5,000 MPa, even more advantageously 600 MPa to 4,000 MPa, even more advantageously 700 MPa to 3,000 MPa, even more advantageously 800 MPa to 2,000 MPa.
[0020] The article of the invention is advantageously flexible and / or foldable about a (bending) axis. Advantageously, the bending axis is arranged perpendicular to the longitudinal axis of the article. The article of the invention is advantageously flexible and / or foldable about a (bending) axis, which is advantageously arranged perpendicular to the longitudinal axis of the article, and the article withstands 100,000 bending and / or folding processes without cracking. The article of the invention is advantageously flexible and / or foldable about a (bending) axis, which is advantageously arranged perpendicular to the longitudinal axis of the article, and the article withstands 200,000 bending and / or folding processes without cracking. One bending and / or folding process may be bending and / or folding the article from an unbent state to a bent state with a bending radius of up to 20 mm, up to 10 mm, up to 5 mm, or up to 2 mm. A bending axis arranged perpendicular to the longitudinal axis of the article is particularly advantageous when the article is used as a display cover, in particular as a protective cover for a display, for example in a smartphone. This bending axis is advantageously arranged such that bending and / or folding essentially divides the article into two halves. By bending and / or folding about such an axis, for example a smartphone or other advantageously portable electronic device, such as an e-book, can be opened or closed.
[0021] Those skilled in the art will appreciate that the above-mentioned advantageous fracture toughness K Ic , compressive stress CS, indentation depth characteristic value x c It is known how to obtain an article having a durability parameter UeP and an article thickness d. However, it was not known to those skilled in the art that the above-mentioned relationship holds between the above-mentioned parameters and the durability parameter UeP, and that an article having excellent load characteristics can be obtained by selecting the parameters such that UeP exceeds 250 MPa. Thus, the present invention enables those skilled in the art to obtain the article of the present invention having excellent characteristics by disclosing the above-mentioned relationship.
[0022] In this invention, "fracture toughness" K Icrefers to the fracture toughness under tensile stress (mode I). This fracture toughness is expressed in units of MPa √m and is advantageously measured by the "pre-cracking method" described in ASTM standard C1421-15 (page 9 ff.). Fracture toughness K Ic is advantageously determined using one or more reference objects. Advantageously, the fracture toughness K Ic The article used to measure K is not tempered, in particular is not chemically tempered. Ic is greater than 0.4MPa √m. Even more advantageously, K Ic is at least 0.45 MPa √m, more advantageously at least 0.5 MPa √m, more advantageously at least 0.6 MPa √m, more advantageously at least 0.7 MPa √m, more advantageously at least 0.8 MPa √m. Ic is at most 100 MPa √m, more preferably at most 75 MPa √m, even more preferably at most 50 MPa √m, even more preferably at most 10 MPa √m, even more preferably at most 8 MPa √m, even more preferably at most 5 MPa √m. Ic is in the range of more than 0.4 MPa·√m and not more than 100 MPa·√m, more preferably in the range of 0.45 MPa·√m to 75 MPa·√m, even more preferably in the range of 0.5 MPa·√m to 50 MPa·√m, even more preferably in the range of 0.6 MPa·√m to 10 MPa·√m, even more preferably in the range of 0.7 MPa·√m to 8 MPa·√m, and even more preferably in the range of 0.8 MPa·√m to 5 MPa·√m.
[0023] In order to further increase the service life when bent, the stress distribution in the article can also be changed. Advantageously, the article is tempered, in particular thermally and / or chemically, particularly advantageously chemically. For example, the article, in particular the glass article, can be chemically tempered by element exchange. In this case, small alkali ions in the article are usually exchanged for larger alkali ions. Typical here is the substitution of the smaller sodium with potassium. However, in the present invention, the very small lithium can also be replaced by sodium or potassium. In the present invention, it is also possible to replace the alkali ions with silver ions. Furthermore, alkaline earth ions can be exchanged for each other in the same principle as the alkali ions. Advantageously, this ion exchange takes place in a bath of molten salt between the surface of the article and a salt bath. Such a bath is also called a "tempering bath". Pure molten salts can be used for the exchange, such as molten KNO3. It is also possible to use mixtures of salts or mixtures of salts with other components. The reliability of the bent article can be further improved by the generation of a defined and adjusted compressive load profile in the article. This can be accomplished by a multi-step chemical exchange process, or by ion implantation to produce the desired compressive bias profile.
[0024] The exchange of smaller ions with larger ions generates a compressive stress in the exchange zone, which, in the case of a single exchange process, decreases from the surface to the center of the glass according to a complementary error function. The maximum compressive stress occurs just below the glass surface and is hereafter referred to as "CS" (compressive stress). CS is stress and is expressed in MPa. Advantageously, CS is measured using an Orihara measuring instrument FSM-60LE.
[0025] Advantageously, CS is greater than 200 MPa. More advantageously, CS is at least 400 MPa, more advantageously at least 600 MPa, and even more advantageously at least 800 MPa. Advantageously, CS is at most 20000 MPa, more advantageously at most 10000 MPa, more advantageously at most 5000 MPa, and even more advantageously at most 3000 MPa. Advantageously, CS is in the range of more than 200 MPa and not more than 20000 MPa, more advantageously in the range of 400 MPa to 10000 MPa, more advantageously in the range of 600 MPa to 5000 MPa, and even more advantageously in the range of 800 MPa to 3000 MPa. The values listed here indicate the absolute value of CS. In the formula of the present invention, CS must be used as a negative number, as explained above.
[0026] The shape of the energization profile after one-step element exchange follows the complementary error function as shown above. The diffusion coefficient D varies for each ion species and also varies with temperature and material. The diffusion coefficient D is expressed in units of m 2 The indentation depth characteristic value x is determined by the diffusion coefficient D and the strengthening treatment time t. c of
number
[0027] "Exchanged ions" as used herein refer to ions whose concentration in the exchange zone has increased relative to their concentration in the base material due to the exchange process of the chemical strengthening treatment. The concentration of exchanged ions decreases from the surface to the interior of the article.
number
number
[0028] In other words, x=x cIn the case of c(x c ) = erfc(1) ≒ 15.73% holds true.
[0029] That is, depth x=x c In this case, the proportion exceeding the base proportion is approximately 15.73% of the maximum proportion at the surface.
[0030] Therefore, the characteristic indentation depth x c teeth, c ion (x c )=c ion (bulk)+0.1573·(c ion (surface)-c ion (bulk) is the depth at which
[0031] In the same formula, c ion (bulk) denotes the concentration of exchanged ions in the base material, and c ion (surface) indicates the concentration of exchanged ions on the surface of the article, and c ion (x c ) is depth x c 4 shows the concentration of exchanged ions at
[0032] The surface of the article of the present invention may be further modified and / or removed (e.g., by etching and / or polishing, etc.) after the toughening treatment. Parameter Fracture Toughness K Ic and compressive stress CS and indentation depth characteristic value x c The relationship of the present invention between the thickness d of the article and the durability parameter UeP also holds true when the surface of the article, especially the glass, is further altered and / or removed after the tempering treatment (e.g. by etching and / or polishing, etc.). In such cases, the following values are used in the formula: Fracture toughness K Ic is calculated as above. · Article thickness d is the thickness after surface treatment. · Compressive stress CS is the value of the compressive stress on the surface after surface treatment. If the surface is further modified after the strengthening treatment, in particular by removing parts of the surface where exchange has taken place (e.g. by etching and / or polishing), then the concentration of exchanged ions at the surface will also change, e.g. by removing surface parts with a particularly high concentration of exchanged ions. Thus the characteristic indentation depth x c is calculated according to the formula below and described above: c ion (x c )=c ion (bulk)+0.1573·(c ion (surface)-c ion (bulk) is determined as the depth at which In the same formula, c ion (bulk) denotes the concentration of exchanged ions in the base material, and c ion (surface) indicates the concentration of exchanged ions on the surface after surface treatment, and c ion (x c ) is depth x c 4 shows the concentration of exchanged ions at
[0033] Indentation depth characteristic value x c The units of are units of length. Advantageously, x c is at least 2 μm, more preferably at least 3 μm, more preferably at least 0.843·4 μm, more preferably at least 4 μm, more preferably at least 6 μm, more preferably at least 8 μm, more preferably at least 10 μm. c is at most 50 μm, more preferably at most 30 μm, even more preferably at most 27 μm, even more preferably at most 25 μm, even more preferably at most 24 μm, even more preferably at most 22 μm, even more preferably at most 20 μm. c is in the range of 2 μm to 50 μm, more preferably in the range of 3 μm to 30 μm, even more preferably in the range of 0.843·4 μm to 27 μm, even more preferably in the range of 4 μm to 25 μm, even more preferably in the range of 6 μm to 24 μm, even more preferably in the range of 8 μm to 22 μm, even more preferably in the range of 10 μm to 20 μm.
[0034] x c It has been found to be advantageous that x does not exceed a certain value in comparison with the thickness d of the article. c is at most d / 2, more preferably at most d / 3, more preferably at most d / 3.5, more preferably at most d / 4, more preferably at most d / 5, more preferably at most d / 6, more preferably at most d / 7. c is at least d / 40, more preferably at least d / 30, more preferably at least d / 27, more preferably at least d / 25, more preferably at least d / 20, more preferably at least d / 15, more preferably at least d / 10. c is in the range of d / 40 to d / 2, more preferably in the range of d / 30 to d / 3, even more preferably in the range of d / 27 to d / 3.5, even more preferably in the range of d / 25 to d / 4, even more preferably in the range of d / 20 to d / 5, even more preferably in the range of d / 15 to d / 6, even more preferably in the range of d / 10 to d / 7.
[0035] Advantageously, x c is at least 2 μm and at least d / 40, more preferably at least 3 μm and at least d / 30, more preferably at least 0.843·4 μm and at least d / 27, more preferably at least 4 μm and at least d / 25, more preferably at least 6 μm and at least d / 20, more preferably at least 8 μm and at least d / 15, more preferably at least 10 μm and at least d / 10. c is at most 50 μm and at most d / 2, more preferably at most 30 μm and at most d / 3, even more preferably at most 27 μm and at most d / 3.5, even more preferably at most 25 μm and at most d / 4, even more preferably at most 24 μm and at most d / 5, even more preferably at most 22 μm and at most d / 6, even more preferably at most 20 μm and at most d / 7.
[0036] The absolute magnitude of the tensile stress for a given bending radius varies approximately linearly with the article thickness d. The greater the article thickness, the greater the bending stress. "Bending stress" refers to the tensile stress on the convex side of the bent article. The thickness of the article can be freely selected by the developer or designer. The thickness of the article is measured in meters [m]. Advantageously, the article thickness d is at most 500 μm, more advantageously at most 450 μm, more advantageously at most 400 μm, more advantageously at most 300 μm. Advantageously, the article thickness d is at least 5 μm, more advantageously at least 20 μm, more advantageously at least 50 μm, more advantageously at least 100 μm. Advantageously, the article thickness d is in the range of 5 μm to 500 μm, more advantageously in the range of 20 μm to 450 μm, more advantageously in the range of 50 μm to 400 μm, more advantageously in the range of 100 μm to 300 μm. Advantageously, the article thickness d is measured using a thickness gauge. It can also be calculated via weight, basis and density. Other suitable methods are possible.
[0037] Moreover, it has been found that the tensile stress on the convex side of the article is in a first approximation directly proportional to the elastic modulus of the transparent brittle material. Therefore, for the life of a bent article, it is advantageous if the elastic modulus of the material is not too high. Advantageously, the elastic modulus is at most 200 GPa, more advantageously at most 150 GPa, more advantageously at most 120 GPa, more advantageously at most 100 GPa. Advantageously, the elastic modulus is at least 40 GPa, more advantageously at least 50 GPa, more advantageously at least 60 GPa, more advantageously at least 70 GPa. Advantageously, the elastic modulus is in the range of 40 GPa to 200 GPa, more advantageously in the range of 50 GPa to 150 GPa, more advantageously in the range of 60 GPa to 120 GPa, more advantageously in the range of 70 GPa to 100 GPa. The elastic modulus is advantageously determined via the sound velocity in the material. Determining the elastic modulus via the sound velocity is conventional and known to the person skilled in the art.
[0038] The life of the bent product can also be increased if the tensile stress is transferred from inside the article to outside. This can be achieved in particular in the present invention by providing another material on at least one side of the article, in particular on the side that is subjected to the tensile stress. The present invention therefore also relates to a composite comprising the article of the present invention and another material provided on at least one side of said article. It is sufficient that the other material is provided on the edges of the article and in the vicinity of the edges of the article. It is not necessary to provide the other material on the entire surface of the article. "In the vicinity of the edges of the article" advantageously refers to an area of the surface of the article that is advantageously at least 10·d and advantageously at most 50·d, more advantageously at most 20·d, from the nearest edge of the article, where "d" denotes the thickness of the article.
[0039] Advantageously, the other material has a modulus of elasticity of more than 10 GPa. Advantageously, the modulus of elasticity of the other material is at least 20 GPa, more advantageously at least 50 GPa, more advantageously at least 75 GPa, and even more advantageously at least 100 GPa. Advantageously, the modulus of elasticity of the other material is at most 1000 GPa, more advantageously at most 800 GPa, more advantageously at most 700 GPa, and even more advantageously at most 650 GPa. Advantageously, the modulus of elasticity of the other material is in the range of more than 10 GPa and not more than 1000 GPa, more advantageously in the range of 20 GPa to 800 GPa, more advantageously in the range of 50 GPa to 700 GPa, and even more advantageously in the range of 100 GPa to 650 GPa.
[0040] Elastic modulus of the article E Artikel In comparison with the modulus of elasticity of the other material, E Artikel / 10~10·E Artikel and more preferably in the range of E Artikel / 5~5·E Artikel and more preferably in the range of E Artikel / 2~2·E Artikel is within the range.
[0041] Advantageously, the brittleness S of the other material is less than 20 μm -1 / 2 less than 10 μm, more preferably -1 / 2 less than 5 μm, more preferably-1 / 2 less than 2 μm, more preferably -1 / 2 less than 1 μm, more preferably -1 / 2 less than 0.5 μm, more preferably -1 / 2 less than 0.25 μm, more preferably -1 / 2 less than 0.1 μm, more preferably -1 / 2 less than 0.05 μm, more preferably -1 / 2 less than 0.005 μm, more preferably -1 / 2 Advantageously, the thickness of the other material is in the range of 0.2·d to 5·d, more advantageously in the range of 0.5·d to 2·d, where d is the thickness of the article. Advantageously, the thickness of the other material is at least 10 μm, more advantageously at least 50 μm, more advantageously at least 100 μm, more advantageously at least 200 μm, more advantageously at least 500 μm. Advantageously, the other material is selected from the group consisting of plastics, in particular polymer plastics, and metallic materials, in particular metals. A particularly advantageous plastic is polyethylene (PE). Advantageously, the other material is a metallic material, very particularly advantageously steel.
[0042] As mentioned above, tensile stresses are transferred from within the article to the other material. It is therefore advantageous if the other material has a relatively high expansion limit. Advantageously, the 0.2% expansion limit of the other material, especially metallic materials, is at least 50 N / mm 2 , and more advantageously at least 75 N / mm 2 , and more advantageously at least 100 N / mm 2 , and more advantageously at least 150 N / mm 2 The 0.2% expansion limit is the (uniaxial) mechanical stress at which, after unloading, the residual expansion of the specimen is exactly 0.2% based on the starting length. The 0.2% expansion limit can be determined unambiguously from the nominal stress vs. total expansion graph.
[0043] It is also advantageous if the other material has a relatively high tensile strength. Advantageously, the other material, in particular the polymer plastic, has a tensile strength of at least 50 N / mm 2 , and more advantageously at least 60 N / mm 2, and more advantageously at least 70 N / mm 2 , and more advantageously at least 80 N / mm 2 The tensile strength is advantageously measured according to the standards EN ISO 6892-1, ISO 6892, ASTM E 8, ASTM E 21, DIN 50154, ISO 527, ASTM D 638.
[0044] Surprisingly, it has further been discovered that geometric phenomena within the article cause a reduction in the compressive bias at the article edges. Such adverse phenomena can be reduced by edge rounding. Surprisingly, the relationship between the article thickness d and the characteristic reinforcement depth value x c and the rounding radius OVR have the following relationship: d / 3>OVR>x c / 5 It has been found to be advantageous to
[0045] Advantageously, therefore, the rounding radius OVR is less than d / 3 and less than x c / 5. The radius of rounding OVR is measured at the transverse crack of the article sheet. Here, OVR corresponds to the radius of the largest possible circle that can be fitted to the edge of the transverse crack when it occurs. This edge is a cross section at the edge of the original sheet. Advantageously, the measurement of the OVR of the individual article is performed indirectly using one or more reference articles from which the OVR of the individual article can be estimated. For example, within a production lot, measurements are not performed directly on the selected article itself, but on one or more reference articles of the same lot, as long as there are no or insignificant differences in parameters between the individual articles of the same lot. Here, "insignificant differences" advantageously means that the difference between the maximum and minimum values of the same lot is at most 20%, more advantageously at most 15%, more advantageously at most 10%, more advantageously at most 5%, more advantageously at most 2%, more advantageously at most 1%.
[0046] In one embodiment, the present invention determines the rounding radius OVR, and determines whether OVR is less than d / 3 and x cIn one embodiment, the present invention relates to a method for arranging an article made of a transparent brittle material, the article being selected such that the radius of curvature OVR is less than d / 3 and greater than x c In one embodiment, the present invention relates to a composite comprising an article made of a transparent brittle material and another material provided on at least one side of the article, the composite comprising an article made of a transparent brittle material and having a radius of curvature OVR of less than d / 3 and greater than x c For composites where the R2 is greater than 5 / 5.
[0047] For the etching, an environment suitable for the removal of material is used. For this purpose, preferably, a liquid containing hydrofluoric acid, such as HF in various concentrations, in particular ammonium acid fluoride, is used. This can be used in mixtures with other liquids, in particular with other acids. The concentration and the etching time can be adjusted accordingly depending on the desired removal. In the present invention, etching can also be carried out in an alkaline liquid. When etching with an alkaline liquid, the etching time is longer compared to etching with HF. Preferred alkaline liquids are caustic potash (KOH) or caustic soda (NaOH). In the present invention, plasma etching can also be used.
[0048] The effect of the compressive loading profile on the service life of the bent article can be demonstrated by carrying out strength measurements on the glass. To do this, a two-point bending measurement was carried out to measure the strength according to the publication by Matthewson and Kurkjian (J. Am. Ceram. Soc., 69
[11] , pp. 815-821, 1986). Advantageously, the measurement of the strength of the individual article is carried out indirectly using one or more reference articles from which the strength of the individual article can be estimated. For example, within a production lot, measurements are not carried out directly on the selected article itself, but on one or more reference articles of the same lot, as long as there is no or no significant difference in the parameters between the articles of the same lot. Here, "non-significant difference" advantageously means that the difference between the maximum and minimum values of the same lot is at most 20%, more advantageously at most 15%, more advantageously at most 10%, more advantageously at most 5%, more advantageously at most 2% and even more advantageously at most 1%.
[0049] The relationship between the mean value (MW) of the measurement sequence, the standard deviation (STABW) of the measurement sequence, the number of samples N included in one measurement sequence, and the strength parameter OFP is as follows:
number
[0050] Advantageously, the OFP is at least 2, and more advantageously, greater than 4. Even more advantageously, the OFP is at least 5, and even more advantageously, at least 10, and even more advantageously, at least 20. Advantageously, the OFP is at most 100, and even more advantageously, at most 80, and even more advantageously, at most 70, and even more advantageously, at most 60. Advantageously, the OFP is in the range of more than 4 and up to and including 100, and even more advantageously, in the range of 5-80, and even more advantageously, in the range of 10-70, and even more advantageously, in the range of 20-60.
[0051] In one embodiment, the invention relates to a method for arranging an article made of a transparent brittle material, the strength parameter OFP being determined according to the formula above and selecting an article having an OFP greater than 4. In one embodiment, the invention relates to an article made of a transparent brittle material, the strength parameter OFP being greater than 4. In one embodiment, the invention relates to a composite comprising an article made of a transparent brittle material and another material provided on at least one side of said article, the composite having a strength parameter OFP greater than 4. More advantageously, the OFP is at least 5, more advantageously at least 10, more advantageously at least 20. Advantageously, the OFP is at most 100, more advantageously at most 80, more advantageously at most 70, more advantageously at most 60. Advantageously, the OFP is in the range of more than 4 and less than or equal to 100, more advantageously in the range of 5 to 80, more advantageously in the range of 10 to 70, more advantageously in the range of 20 to 60.
[0052] In brittle materials, subcritical crack growth can occur, where microdefects can grow and "grow" into the critical region, even for subcritical loads (i.e., load cases that do not directly result in fracture), and cause delayed fracture. Typically, the crack growth rate is expressed as a function of the relative stress intensity factor v, and is given by the formula v = v0(K I / K Ic ) n We can see an exponential relationship that follows.
[0053] Surprisingly, it has been found that, for a constant tensile stress, the influence of the air humidity is much more important in order to achieve a long life expectancy than the exponent n, also called "n value", which is a material parameter. In particular, it has been found that articles suitable for use as bendable articles have a large variation in the prefactor v0 in the above formula when the air relative humidity varies within a range between 20% rH and 70% rH. Advantageously, when the air relative humidity varies within a range between 20% rH and 70% rH, the prefactor v0 varies by a factor of more than 15, even more advantageously by a factor of more than 20, even more advantageously by a factor of more than 25, even more advantageously by a factor of more than 30 and even more advantageously by a factor of more than 50.
[0054] In one embodiment, the invention relates to a method for arranging an article made of a transparent brittle material, selecting an article whose pre-factor v0 varies by a factor of more than 15, more advantageously more than 20, more advantageously more than 25, more advantageously more than 30, more advantageously more than 50, when the relative humidity in the air varies in the range between 20% rH and 70% rH. In one embodiment, the invention relates to an article made of a transparent brittle material whose pre-factor v0 varies by a factor of more than 15, more advantageously more than 20, more advantageously more than 25, more advantageously more than 30, more advantageously more than 50, when the relative humidity in the air varies in the range between 20% rH and 70% rH. In one embodiment the invention relates to a composite comprising an article made of a transparent brittle material and another material provided on at least one side of said article, in which the pre-factor v0 varies by a factor of more than 15, more advantageously by a factor of more than 20, more advantageously by a factor of more than 25, more advantageously by a factor of more than 30, more advantageously by a factor of more than 50 when the relative humidity in the air varies within the range between 20% rH and 70% rH.
[0055] In the case of impact loading, very localized stress overshoots occur, consisting of compressive loads at the center of the impact and tensile loads at its edges. The article must, as usual, absorb both components of the energy E of the impact object and the impulse p. The energy is
number
number
[0056] The crack initiation load describes the ability of an article to resist crack formation when penetrated by an object. The crack initiation load is essentially applicable when it occurs during impact loading. A relatively high crack initiation load is therefore advantageous. At a relative humidity of 50% in the air, the crack initiation load of the article is advantageously at least 1.5 N, more advantageously at least 3 N, even more advantageously at least 5 N, even more advantageously at least 10 N. Advantageously, at a relative humidity of 50% in the air, the crack initiation load is at most 200 N, even more advantageously at most 150 N, even more advantageously at most 75 N, even more advantageously at most 65 N, even more advantageously at most 55 N, even more advantageously at most 45 N, even more advantageously at most 30 N. Advantageously, the crack initiation load is in the range of 1.5 N to 200 N, even more advantageously in the range of 3 N to 150 N, even more advantageously in the range of 5 N to 75 N, even more advantageously in the range of 10 N to 30 N. The crack initiation load is advantageously determined using a Vickers indenter as described by Sehgal and Ito (J. Am. Ceram. Soc., 81 [9], pp. 2485-2488, 1998).
[0057] Another important aspect during impact loading is the critical compression ratio. This is the limiting compressive stress that the material can withstand before it becomes prone to cracking. This quantity corresponds to expansion and is unitless. Advantageously, the critical compression ratio of the article is at least 8%, more advantageously at least 10%. This critical compression ratio can be determined by a cylindrical compression method. Advantageously, the article sample to be tested is placed between the end faces of two cylinders so that pressure can be applied to the article sample to be tested through both cylinders. A universal testing machine, for example an INSTRON 6025 type, can be used to apply the compressive force.
[0058] For strength against impact load, the elastic modulus E and fracture toughness K Ic For a given geometric shape of the striking tool, the maximum compressive load of the article is
number
[0059] Scratching involves the displacement or intrusion of hard material on the glass surface, which can lead to unattractive scratches caused by chippings and plastic deformation, and in some cases to the formation of cracks that can penetrate deep into the article and cause its destruction there. There are several ways in which scratches can be countered:
[0060] It is advantageous if the transparent brittle material is hard. Surprisingly, it has been found that it is not the Vickers hardness but the Martens hardness that is important. The Vickers hardness (e.g. of glass) is known as a common hardness parameter for measuring, e.g., brittleness. For the Vickers hardness, a pyramidal diamond is pressed into the glass and the indentation left after unloading is geometrically measured. From this measurement the hardness is determined. This hardness is therefore a measure of the plastic deformation of the material. In contrast, when measuring the Martens hardness, the indentation depth or the contact area for a given applied force is measured. This hardness therefore gives information about the elastic deformation of the material. Surprisingly, it has been found that the Martens hardness is a better measure of the resistance capacity of the glass. The reason for this is that when measuring the Martens hardness, the stress ratio under the indenter is much more similar to the stress ratio when the article is loaded. This means that the fracture of the article, and especially of the glass, occurs during loading (especially in the case of impact loading).
[0061] Advantageously, the material has a Martens hardness of at least 1000 MPa, more advantageously at least 1200 MPa, more advantageously at least 1500 MPa, more advantageously at least 2000 MPa. Advantageously, the Martens hardness is at most 30000 MPa, more advantageously at most 25000 MPa, more advantageously at most 20000 MPa, more advantageously at most 16000 MPa. Advantageously, the Martens hardness is measured according to DIN EN ISO 14577.
[0062] It has further been found to be advantageous for Cs to be relatively large, thereby avoiding deep reaching cracks. Advantageously, Cs is greater than 200 MPa. Even more advantageously, Cs is at least 400 MPa, even more advantageously, Cs is at least 600 MPa, even more advantageously, Cs is at least 800 MPa.
[0063] In addition, the indentation depth characteristic value x cIt is advantageous to have a large x since it is possible to avoid so-called "center-tension" cracks, even if some deep cracks occur, and thus not cause the plate to split. c is at least 2 μm, more preferably at least 3 μm, more preferably at least 4 μm, more preferably at least 6 μm, more preferably at least 8 μm, and more preferably at least 10 μm.
[0064] The present invention also relates to the use of the article or composite of the present invention as a display cover, especially as a display cover for a smart phone, tablet and / or TV device. [Brief description of the drawings]
[0065] [Figure 1] FIG. 1 shows the relationship between the measured bending radius (characteristic value according to Weibull statistics) and the calculated UeP value (quadratic y-axis) based on an example glass with d=100 μm, KIc=0.7 MPa √m and CS=−960 MPa. The two reference values show the bending radius or UeP value of the untempered glass. [Diagram 2] FIG. 1 shows the relationship between the measured bending radius (characteristic value according to Weibull statistics) and the calculated UeP value (quadratic y-axis) based on another example glass with d=100 μm, KIc=0.7 MPa √m and CS=−440 MPa. The two reference values show the bending radius or UeP value of the untempered glass. [Diagram 3] Figure 1 shows UeP as a function of bending radius. The two small data points with UeP values below 200 MPa are reference values for untempered glass. [Figure 4] Figure 1 shows UeP as a function of fracture stress. The two small data points with UeP values below 200 MPa are reference values for untempered glass. [Diagram 5]FIG. 1 is a graph showing UeP values of three glasses having different compressive stresses CS as a function of xc. [Figure 6] FIG. 1 is a graph showing the UeP values of four glasses each having a different thickness d as a function of xc. [Figure 7] FIG. 1 is a graph showing the UeP values of four glasses each having a different thickness d as a function of xc. [Figure 8] FIG. 1 is a graph showing the UeP values of three glasses each having a different fracture toughness KIc as a function of xc. [Figure 9] FIG. 1 is a graph showing the UeP values of three glasses each having a different fracture toughness KIc as a function of xc. EXAMPLES
[0066] 1. Procure multiple items from multiple different manufacturing lots. Fracture toughness K of each item Ic , compressive stress CS, indentation depth characteristic value x c and the article thickness d are measured. The above parameters of each article are measured for each production lot based on 10 reference articles each representing each lot. Based on the parameter measurements, the following formula is used:
number
number
number
number
number
[0067] Not selected here are, in particular, articles having a UeP not exceeding 250 MPa. The selected articles are separated from the other articles and grouped together in a set of articles according to the invention.
[0068] 2. Surprisingly, it has been discovered that the higher the UeP of the glass, the smaller the bend radius that the glass can be bent to before breaking.
[0069] In FIG. 1, the relationship between the measured bending radius (characteristic value according to Weibull statistics) and the calculated UeP value (quadratic y-axis) can be seen on the basis of an example glass. The two reference values show the bending radius or UeP value of untempered glass. It can be seen that the UeP value is maximum for the smallest bending radius. This means that a high UeP value allows small bending radii to be achieved. The measurements were carried out by the two-point bending method (see also Matthewson and Kurkjian (J. Am. Ceram. Soc., 69
[11] , pp. 815-821, 1986)). As bending radius in the two-point bending method, half the distance between the plates at which the glass breaks is defined in the figure.
[0070] Figure 2 shows a comparable graph for another glass with only a force of -440 MPa (see graph center). It can be seen that the achievable bending radius is significantly higher than for the glass with CS=-960 MPa and the UeP curve is significantly lower. Smaller bending radii can therefore be achieved with a higher force. These measurements were carried out with the step roller described in DE 10 2014 110 855 A1. The bending radius in the figure is the radius of the roller at which the glass breaks.
[0071] Plotting the data for both glasses gives two graphs: UeP as a function of bending radius, shown in FIG. 3, and UeP as a function of breaking stress, shown in FIG. 4 (the higher the stress, the smaller the bending radius). It can be seen that with higher UeP values, smaller bending radii can be achieved. Higher UeP values translate to higher breaking stresses. The two small data points with UeP values below 200 MPa are reference values and also represent glasses that cannot be tempered or have very low CS values.
[0072] 5 to 9 are graphs showing durability parameters as a function of other parameters. The x-axis is always x c Two other parameters are fixed and the third parameter is varied across the curve. Which parameters are fixed and at what values is indicated in the title of each figure.
[0073] In Figure 5, it can be seen that an increase in the force CS leads to an increase in the durability parameter UeP. In Figures 6 and 7, it can be seen that an increase in the article thickness correlates with a higher UeP value. In Figures 8 and 9, it is clear that an increase in the fracture toughness KIc correlates with a higher UeP value.
Claims
1. An article made of a chemically strengthened borosilicate glass, an aluminosilicate glass, or an aluminoborosilicate glass, comprising: The proportion of Li 2 O + Na 2 O in the glass is more than 5% by weight, The Martens hardness is at least 1000 MPa, The article has a fracture toughness of K Ic , compressive stress CS, and indentation depth characteristic value x c and an article thickness d; With respect to the said article, [0010] is satisfied, Where: [0025] If [0030] and [0045] then B=0; [0050] then B=0, and m = 1 meter, x c is at least 2 μm, and UeP is at least 800 MPa, CS is at least 800 MPa, and The article is included in a set of articles including the article and, additionally, at least one other article made of chemically strengthened glass, the Martens hardness being at least 1000 MPa; The other article has a fracture toughness of K Ic , compressive stress CS, and indentation depth characteristic value x c and an article thickness d; Regarding the other items, [006] is satisfied, Where: [0070] If [0080] and [0090] then B=0; [0010] then B=0, and m = 1 meter, x c is at least 2 μm, and The article, wherein UeP is at least 800 MPa and CS is at least 800 MPa.
2. x c is at least 6 μm; The article of claim 1.
3. x c is at least d / 15; 3. The article of claim 1 or 2.
4. The elastic modulus of the glass is in the range of 40 GPa to 200 GPa; An article according to any one of claims 1 to 3.
5. The fracture toughness K Ic is greater than 0.4 MPa √m; An article according to any one of claims 1 to 4.
6. The indentation depth characteristic value x c is a maximum of 50 μm; An article according to any one of claims 1 to 5.
7. The article thickness is in the range of 5 μm to 500 μm; The article of any one of claims 1 to 6.
Citation Information
Patent Citations
Durable glass housing / enclosure for electronic devices
JP2012500177A
Flexible ultra-thin chemically strengthened glass
JP2016508954A
Flexible glass stack assembly, article, and method for manufacturing the same
JP2016539067A
Glass member and manufacturing method of glass member
JP2017075078A
Cover glass
WO2013051514A1